Circle-based model to estimate error in using the lowest points to indicate locations of contact developed by the femoral condyles on the tibial insert in total knee arthroplasty. (7th May 2021) - Simileysky, Alexander; Ridenour, Delaney; Hull, M.L.
Abstract: A common method used to study tibiofemoral joint biomechanics following total knee arthroplasty (TKA) is the lowest point method, which finds the lowest points of each femoral condyle in relation to the plane of the resected tibia. The objectives of this paper were twofold: 1) to use a circle-based model to demonstrate the large inherent error introduced when the lowest points are used to indicate anterior-posterior (AP) positions of contact by the femur on the tibial insert, 2) to use the circle-based model to estimate the magnitude of error. A circle-based model was created to simulate articular surfaces of the tibial insert and condyles of the femoral component and to demonstrate the error. Equations relating the error to radii of tibial and femoral articular surfaces were derived. The magnitude of the error was estimated for common low-conforming TKA components by determining radii using best-fit circles to approximate curvature of articular surfaces. Error in AP tibial insert contact locations is caused by the slope of the tibial articular surface and the magnitude increases with increasing slope and increasing radius of the femoral condyle. For radii approximating articular surfaces of common low-conforming components, relative errors range from 45% to 109%. The circle-based model effectively demonstrates the cause of the large error in using lowest points to indicate AP tibial insert contact locations and enables an estimate of relative error. Because relative error exceeds 45%, the lowest point method should not be used to indicate the AP tibial insert contact locations.